PENGARUH METODE PEMBELAJARAN INQUIRY DAN MOTIVASI SISWA TERHADAP PRESTASI BELAJAR SEJARAH PADA SISWA KELAS X IIS DI SMA N 6 SURAKARTA TAHUN PELAJARAN 2014/20151 - Ikhsanti, Akhmad Arif Musadad, Musa Pelu, Novtia (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2015)
The purpose of this research to study and to find out: 1) the influence of inquiry learning method and lecture to learning achievement of history; 2) the difference in effect between students who have a high learning motivation with students who have a low learning motivation to learning achivement of history; 3) The interaction effect of inquiry learning methods and student motivation toward learning achievement history.This research is descriptive quantitative research with the conclusion through statistical analysis. The population in this study were all students of class X SMA IIS 6 Surakarta academic year 2014/2015. Samples taken as many as 120 students. Samples were taken at random cluster sampling technique. Necessary data obtained through questionnaires and documentation. Data analysis techniques are used analysis of variance (ANOVA).The conclusion of the study as follows: 1) There is a significant difference between the use of methods of inquiry and discourse on the learning achievement of subjects with a history of Fcount = 16.132> F table = 4.00. History lesson learning achievement in the group of students with learning methods inquity tend to be higher compared with subjects learning achievement of students with a history of group teaching methods lectures; 2) There is a significant difference between students who have learning motivation high and low on the learning achievement of subjects History class X SMA IIS 6 Surakarta first semester of 2014/2015 Fcount= 6.512> F table = 4.00. History lesson learning achievement in the group of _______________________1 Ringkasan Penelitian Skripsi2 Mahasiswa Program Studi Penedidikan Sejarah Universitas Sebelas Maret3 Dosen dan Pembimbing pada Program Studi Pendidikan Sejarah, FKIP UNS, Surakartastudents who have a high level of learning motivation tends to be higher than the achievement of study subjects who had a history of a group of students learningmotivation level is low; 3) There is a significant interaction effect between the use of teaching methods and students' motivation towards learning achievement subjects with a history of values of Fcount = 4.408> F table = 4.00. Thus, it can be seen that a more effective method of inquiry used in learning activities to improve achievement and motivation to learn subjects History of SMA Negeri 6 Surakarta.